Advertisement Remove all ads

The sum of three numbers is 6. When second number is subtracted from thrice the sum of first and third number, we get number 10. - Mathematics and Statistics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Sum

The sum of three numbers is 6. When second number is subtracted from thrice the sum of first and third number, we get number 10. Four times the sum of third number is subtracted from five times the sum of first and second number, the result is 3. Using above information, find these three numbers by matrix method.

Advertisement Remove all ads

Solution

Given that the sum of three numbers, x, y and z is 6.
From the given statement, we have,
x + y + z = 6
3 ( x + z ) -  y = 10 
5 ( x + y ) -  4z = 3
Thus, the system of equations are :
x + y + z = 6                                 (i)
3x - y + 3z = 10                            (ii)
5x + 5y - 4z = 3                            (iii)
Let us write the above equations in the matrix form as:

`[[1,1,1],[3,-1,3],[5,5,-4]][[x],[y],[z]]=[[6],[10],[3]]`

AX = B

`"A" = [[1,1,1],[3,-1,3],[5,5,-4]], "X" = [[x],[y],[z]],  "B" = [[6],[10],[3]]`

Applying R3→ R3- 5R1 , we have

`[[1,1,1],[3,-1,3],[0,0,-9]][[x],[y],[z]]=[[6],[10],[-27]]`

 Applying R2 → R2 - 3R1 , we get
`[[1,1,1],[0,-4,0],[0,0,-9]][[x],[y],[z]]=[[6],[-8],[-27]]`

Thus,
x + y + z = 6                                   [From(i)]
- 4y = - 8                                                 (iv)
- 9z = - 27                                                (v)
From equation (iv), we get
y = 2
From equation (v), we get
z = 3
Putting the value of y and z in equation (i), we get x = 6 - 2 - 3 = 1
Hence, numbers are 1, 2, and 3.

Concept: Elementary Transformations
  Is there an error in this question or solution?

APPEARS IN

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×